TOURISM AND ITS DIFFERENT TYPES WITH THE DEFINTIONS (Ustozlar uchun, 2026)
Tourism is the temporary movement of people to destinations outside their usual environment for leisure, business, or other purposes, involving a stay of at least one night but less than one year. It is a major industry providing services such as transportation, accommodation, and entertainment to travelers.